2011
DOI: 10.1136/annrheumdis-2011-200477
|View full text |Cite
|
Sign up to set email alerts
|

Pulse versus daily oral cyclophosphamide for induction of remission in ANCA-associated vasculitis: long-term follow-up

Abstract: Pulse cyclophosphamide is associated with a higher relapse risk than DO cyclophosphamide. However, this is not associated with increased mortality or long-term morbidity. Although the study was retrospective, data was returned in 90% of patients from the original trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
182
4
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 360 publications
(209 citation statements)
references
References 19 publications
10
182
4
13
Order By: Relevance
“…In those patients with AAV and active GN (creatinine ,5.7 mg/dl [500 mmol/L]), a pulsed regime induced remission as well as the daily oral regimen, with a decreased cumulative dose and fewer instances of leukopenia (9). Although long-term data demonstrated that the pulsed CYP regimen was associated with higher relapse rates, there was no difference in mortality or morbidity (10).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In those patients with AAV and active GN (creatinine ,5.7 mg/dl [500 mmol/L]), a pulsed regime induced remission as well as the daily oral regimen, with a decreased cumulative dose and fewer instances of leukopenia (9). Although long-term data demonstrated that the pulsed CYP regimen was associated with higher relapse rates, there was no difference in mortality or morbidity (10).…”
Section: Introductionmentioning
confidence: 80%
“…This study comprises too few patients to address this issue. Short-and long-term follow-up of patients from the CYCLOPS study (randomized trial of daily oral versus pulsed cyclophosphamide) reported more relapses in the pulsed CYP group (9) with no differences in renal relapses, and importantly no difference in long-term renal outcome or mortality (10).…”
Section: Discussionmentioning
confidence: 99%
“…146 However, for polyangiitis with granulomatosis a randomized trial of daily oral dosing versus intravenous cyclophosphamide (the CYCLOPS trial) showed that oral dosing was more effective in the long term. 147 I have no experience of intravenous administration. 109 Tauber 1991: 105 patients.…”
Section: Use Of Systemic Immunomodulation To Control Immunemediated Imentioning
confidence: 99%
“…Our patient was placed on daily oral CYC along with corticosteroids, since she had an increased risk of relapse due to her age and rapidly worsening kidney function, as well as the presence of the sclerosis pattern in the tissue specimen. Harper et al evaluated the long-term outcomes of the 148 patients previously enrolled in the CYCLOPS study (35). At a median duration of 4.3 years, patient survival was similar between the 2 treatment arms, despite an increased risk of relapse in patients treated with pulse CYC (35).…”
Section: Discussionmentioning
confidence: 99%
“…Harper et al evaluated the long-term outcomes of the 148 patients previously enrolled in the CYCLOPS study (35). At a median duration of 4.3 years, patient survival was similar between the 2 treatment arms, despite an increased risk of relapse in patients treated with pulse CYC (35). In addition, our patient's serum creatinine rapidly worsened during her hospitalization, with a serum creatinine level Ͻ500 moles/liter (5.7 mg/dl), suggestive of severe and rapidly progressive renal vasculitis, immediately life-threatening disease, and poor renal outcome at a 1-year interval (30); therefore, she was treated with a course of plasma exchange (7 sessions in 2 weeks) in conjunction with the prednisone and oral CYC.…”
Section: Discussionmentioning
confidence: 99%